1 Dissolved oxygen measurements on Uberabinha River for determining the oxygenation constant - SILVA MARTINS ALMEIDA, JULIANO; RIBEIRO FRANCO JUNIOR, MOILTON (Águas Subterrâneas, 2013)
Eight stations were chosen, in the twenty-one kilometers of the Uberabinha River, for DO measurements. As a result, two different modeling approaches were adopted to calculate the oxygenation constant (k1). In this paper, the modeling results of the segment of the river in Brazil are presented. Experimental data provides a very useful tool to calculate the oxygenation constant (k1). DO measurements can help the analyses of all weekly and positions variations of dissolved oxygen, replacing the unique value of one measurement in two models. The results of deoxygenation and reaeration constants versus time have shown a representative overview of the surface water quality status.